DR3TBDTT Based Ternary Blends Containing Conjugated Polymers: Crystallization Determines Morphology and Performance. Issue 5 (3rd April 2018) - Yin, Jingping; Zhou, Weihua; Ai, Qingyun; Meng, Xiangchuan; Liu, Siqi; Yu, Zoukangning; Zeng, Jianrong; Chen, Yiwang
Abstract: How the conjugated polymers affect the crystallization of DR3TBDTT, in addition to the corresponding morphology and performance, is not well understood. In this work, the weakly crystalline polymer PTB7‐Th and highly crystalline polymers of PCDTBT and P3HT were incorporated into DR3TBDTT:PC71 BM system to investigate the variation of crystallization, morphology and performance. It is demonstrated that PTB7‐Th is the most effective additive to improve the PCE value of DR3TBDTT:PC71 BM to 5.7%, showing the nucleating agent reducing the crystallization correlation length (CCL) value of DR3TBDTT from 18.7 nm to 17.0 nm, in addition to the optimized morphology. In contrast, the PCDTBT and P3HT could induce the crystallization of DR3TBDTT, leading to much higher CCL value as well as obvious phase separation. Despite of energy level alignment, the crystallization of DR3TBDTT influenced by polymers determines the corresponding morphology of active layers and photovoltaic performance. Abstract : How the conjugated polymers affect the crystallization of DR3TBDTT, in addition to the corresponding morphology and performance, is not well understood. We introduced PTB7‐Th, PCDTBT and P3HT to investigate the influence of crystallization. We found that despite of energy level alignment, the crystallization of DR3TBDTT influenced by polymers determines the corresponding morphology of active layers and photovoltaic performance.